2014
DOI: 10.1021/nl404727m
|View full text |Cite
|
Sign up to set email alerts
|

A Universal Law for Cell Uptake of One-Dimensional Nanomaterials

Abstract: Understanding cell interaction with one-dimensional nanomaterials, including nanotubes, nanowires, nanofibers, filamentous bacteria, and certain nanoparticle chains, has fundamental importance to many applications such as biomedical diagnostics, therapeutics, and nanotoxicity. Here we show that cell uptake of one-dimensional nanomaterials via receptor-mediated endocytosis is dominated by a single dimensionless parameter that scales with the membrane tension and radius of the nanomaterial and inversely with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
110
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(117 citation statements)
references
References 54 publications
6
110
1
Order By: Relevance
“…The methodology can be potentially extended to study important mechanical problems of biological cells. For example, both bending rigidity and membrane tension are found to play critical roles in nanoparticle-cell membrane interaction [35]. The current approach promises consistent and specific property differentiation, in contrast to the deformation-based, bulkaveraged measurements [36].…”
mentioning
confidence: 91%
“…The methodology can be potentially extended to study important mechanical problems of biological cells. For example, both bending rigidity and membrane tension are found to play critical roles in nanoparticle-cell membrane interaction [35]. The current approach promises consistent and specific property differentiation, in contrast to the deformation-based, bulkaveraged measurements [36].…”
mentioning
confidence: 91%
“…3,4 Therefore, there is an urgent need for a better understanding of the interaction between NPs and cell membranes. 5 At present, a large number of experimental and theoretical studies have demonstrated that the size, [6][7][8][9][10] shape, [11][12][13][14][15][16][17][18][19][20] orientation, [21][22][23][24][25][26] stiffness, [27][28][29][30][31] and surface properties [32][33][34][35] of NPs will affect the cellular uptake of NPs. Recent experimental studies have shown that when the radius of the NPs is less than 15 nm, a group of NPs can be internalized by cells or polymersomes as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…However, SEM images are only capable of showing the MCNTs in the membrane, whereas MCNTs still inside or those that have escaped from the cells cannot be visualized. A recent study of interaction between 1D nanomaterial and cell membrane revealed a nearperpendicular entry mode and near-parallel adhesion mode (32). In our study, MCNTs were aligned to the magnetic pulling force.…”
Section: Resultsmentioning
confidence: 49%